Contributions to knowledge of some Southern African fossil sites and their fossils - Van Dijk, D. E. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Botany and Zoology. Palaeontology))--University of Stellenbosch, 2001.